MENINGKATKAN NILAI AKUNTABILITAS MELALUI PEMBANGUNAN DAERAH TEMATIK - Yoki Tulus Sabtian; Akil Fitra Sholakodin; Durratun Nashihah (PANGRIPTA, 2022)
Bureaucratic reform contains areas of change in the management of the human resources of the apparatus itself, which aims to create an effective and efficient bureaucracy. Researchers will review in depth the mechanisms and results of the performance of the Ngawi district government in carrying out development tactics before and during the pandemic, and performance achievements after the regional economic recovery period. This study uses a qualitative approach that focuses on efforts to increase the value of regional SAKIP through thematic regional development. Thematic regional development is adjusted to regional potential and regional superior programs, where Ngawi Regency focuses on regional potential, namely agriculture, trade, and industry. The results of the study indicate that in carrying out development tactics before and during the pandemic, and the achievement of performance after the regional economic recovery period, which is seen from three sectors namely Agriculture, Trade, and Industry, it was found in the last 5 (five) years experienced fluctuating performance.